Compendium of Abstracts of the 5th Philippine Computing Science Congress. - Saldana, Rafael P., Ph D.
A compendium of abstracts of the papers presented during the 5th Philippine Computing Science Congress (PCSC 2006) held on March 4-5, 2005 at the University of Cebu (Banilad Campus), Cebu City is included in this paper. PCSC 2005 was organized by the Computing Society of the Philippines (CSP) and endorsed by the Philippine Commission on Higher Education (CHED).
Keywords: Abstracts; Philippine Computing Science Congress; Computing Society of the Philippines